2003
DOI: 10.1037/0882-7974.18.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: Aging and functional spatial relations in comprehension and memory.

Abstract: Previous research has suggested that, relative to younger adults, older adults devote a greater proportion of their discourse processing to the situation model level. The current experiment assessed whether this is due, in part, to a preserved ability to focus on functionally appropriate information. The focus here was on spatial relations. Both reading time and recognition data showed superior performance for functional over nonfunctional information, and this functional effect was similar in younger and olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 28 publications
7
51
0
1
Order By: Relevance
“…The studies discussed above demonstrated that younger and older adults tend to integrate information into the causal structure of the situation model (Radvansky, Copeland, & Zwaan, 2003). They also represent prominent and integral components of the situation model in a similar manner (Morrow et al, 1992).…”
Section: Age-invariant Cognitionmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies discussed above demonstrated that younger and older adults tend to integrate information into the causal structure of the situation model (Radvansky, Copeland, & Zwaan, 2003). They also represent prominent and integral components of the situation model in a similar manner (Morrow et al, 1992).…”
Section: Age-invariant Cognitionmentioning
confidence: 99%
“…The general result is that older adults perform more poorly on the surface form and textbase levels than do the younger adults. However, at the situation model level, older adults do as well as or better than the younger adults Radvansky, Copeland, & Zwaan, 2003;). This suggests that memory at the situation model level is relatively resilient, as compared with other age-related declines.…”
Section: Creation Of Dynamic Situation Models In Texts: Updatingmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, if a narrated event was not expected, causally relevant spatial relations may be represented because the recipient tries to construct an explanation for the event (Trabasso & Suh, 1993). In several studies that explored similar ideas, causal relevance proved to be crucial for spontaneous spatial representation under the labels functionality of spatial relations (Radvansky & Copeland, 2000;Radvansky, Copeland, & Zwaan, 2003), relevance for protagonist's goals (Levine & Klin, 2001;Morrow, Bower, & Greenspan, 1990), or required for comprehension (Glenberg & McDaniel, 1992;Hakala, 1999).…”
Section: Causal Relevancementioning
confidence: 99%